Students’ Needs and Vocabulary Development in English for Specific Purposes Course - PIYADA LOW (Yayasan Visi Intan Permata, 2018)
Vocabulary is very important for language learners. Limited knowledge of vocabulary can cause problems in language learning, especially in English for Specific Purposes (ESP). Students’ needs on English vocabulary should be invested for learning achievement. The research study was conducted with all students registering in an ESP course, English for Food and Beverage Service. The total number was 54 students: 48 females and 6 males. Three instruments were employed: first and post-activity questionnaires, task assignment, and a vocabulary test. The food lists in the questionnaires fall into five groups: herbs, spices, and food seasonings; vegetables; fruits; meat and poultry; fish and shellfish. Vocabulary list with more than 50% chosen as needed in each food group from the first questionnaire distributed at the beginning of the course were used to create a test on students’ vocabulary knowledge. Two most chosen food groups for vocabulary knowledge development were herbs, spices, and food seasonings group (98.1%) and fish and shell fish group (96.3%). Fish and shellfish list was the only group indicated as a very great problem for the students (48.1%). Vocabulary test results showed the lowest score of 0/23 while the highest score is 22/23 from fish and shellfish group list. Mean of the fish and shellfish food list is 10.80 which is the lowest mean among the five group lists on the vocabulary test. 63% of the students admitted that task assignment responded to their needs of English food vocabulary development.